Taxonomic notes on the genus Brachypterum (Fabaceae: Millettieae) - Song, Zhu-Qiu (Phytotaxa, 2023)
Brachypterum was highly supported as a distinct genus from Derris within the tribe Millettieae by recent molecular and mophological evidence. Brachypterum pseudorobustum (basionym: Derris pseudorobusta) and Derris robusta var. assamica were originally described on fruiting collections from Northeast India, and their flowers were never described. The former species was considered be unique in having habit of scandent shrub, 15-foliolate leaves with minutely puberulous hairs, and one-winged pods usually with multiple seeds per pod. The latter taxon is still remained in Derris, although D. robusta has been accepted as Brachypterum robustum. However, our comparision of characters suggests the former species is quite similar with B. eriocarpum in various characters including its habit, leaf and pod traits, and the latter taxon most closely matches the features of Robinia pseudoacacia from the tribe Robinieae. As a result, Brachypterum pseudorobustum and Derris robusta var. assamica are both excluded from the accepted species list of Brachypterum in this study. A key to all the eleven accepted species of Brachypterum is first provided.